Cryptococcal Meningitis in an Apparent Immunocompetent Patient - Marian Poley MS; Richard Koubek MD; Leonard Walsh MD; Brian McGillen MD (SAGE Publishing, 2019)
Cryptococcal meningitis is an uncommon and severe infection that tends to affect immunocompromised hosts worldwide and in the United States. Annually it is estimated that there are 200 000 cases of cryptococcal meningitis, with the most recent estimate of 3400 cases per year in the United States alone. However, despite the low incidence, 1-year mortality is estimated at 20% to 30% even with long-term consolidation antifungal therapy. A 37-year-old man presented to the emergency department with headaches, dysarthria, hallucinations, and acute worsening of altered mental status, and he was found to have increased intracranial pressure, cerebrospinal fluid leukocytosis, and few encapsulated yeasts consistent with Cryptococcus neoformans meningitis in addition to radiologic evidence consistent with a cryptococcoma of the lungs. This report highlights the occurrence of Cryptococcus neoformans meningitis in a presumed immunocompetent host. The clinician should be aware of sources of minor immunosuppression, as they may contribute to development of Cryptococcus neoformans meningitis. Mortality in this condition remains high due to subacute presentations and delayed diagnosis in non-immunocompromised patients.